RNR principles in practice in the management and treatment of sexual abusers - Jung, Sandy (Safer Society Press, 2017)
Acknowledgments -- Introduction -- An overview of the risk-need-responsivity (RNR) model -- The risk principle -- The need principle -- The responsivity principle -- Illustrative case examples -- Implementation challenges -- Communicating RNR -- Concluding thoughts -- References